Clinicopathologic investigation of methotrexate-induced lymphoproliferative disorders, with a focus on regression. Issue 5 (4th May 2018) - Tokuhira, Michihide; Saito, Shuntaro; Okuyama, Ayumi; Suzuki, Katsuya; Higashi, Morihiro; Momose, Shuji; Shimizu, Takayuki; Mori, Takehiko; Anan-Nemoto, Tomoe; Amano, Koichi; Okamoto, Shinichiro; Takeuchi, Tsutomu; et al.
Abstract: Although recent accumulative data reveal the clinicopathogenesis of regression in methotrexate-induced lymphoproliferative disorders (MTX-LPDs), the precise understanding including this category remains controversial. In this study, we analyzed 62 patients with MTX-LPD. Forty-three patients showed regression (Reg group), with high rates of Hodgkin lymphoma (HL) and LPD (90 and 88%, respectively). Among the 43 patients of the Reg group, 14 patients (33%) relapsed. The median duration before relapse in the Reg group was 10.6 months. Although the difference of OS between the Reg and Non-Reg groups was not significantly different, relapse-free patients in the Reg group had a superior overall survival (OS). MTX duration had a significant impact on Epstein–Barr virus (EBV) infection ( p  = .00131). Furthermore, EBV infection was significantly related to clinical manifestations, including spleen invasion, in the regression phenomenon. Some human leukocyte antigens (HLA) alleles might affect MTX-LPD development via EBV infection, although A*2402 and DRB1*0405 might be affected as fundamental factors.